(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
According to literature data, purulent-inflammatory diseases of the maxillofacial region (MFR) account for 40% to 60% of the total number of surgical dental diseases. Issues regarding the organization of care for patients with purulent-inflammatory diseases of the maxillofacial region remain relevant. Currently, the main treatment method for patients with purulent-inflammatory diseases of the maxillofacial region is comprehensive therapy, which involves combining surgical procedures (abscess incision, drainage, etc.) with the use of pharmacological agents. Prognosis of purulent-inflammatory processes in the maxillofacial region is one of the pressing issues in dentistry due to the high prevalence of these diseases, the severity of the clinical course, and the possibility of developing life-threatening complications.